Prospective phase-II-study evaluating postoperative radiotherapy of cervical and endometrial cancer patients using protons - the APROVE-trial - Arians, Nathalie; Lindel, Katja; Krisam, Johannes; Herfarth, Klaus; Krug, David; Akbaba, Sati; Oelmann-Avendano, Jan Tobias; Debus, Jürgen (Radiation oncology, 2017)
The prognosis for patients with cervical or endometrial cancer has improved over the last decades. Thus, reducing therapy-related toxicity and impact on quality of life have become more and more important. With the development of new radiotherapy techniques like IMRT (Intensity-modulated radiotherapy) the incidence of acute and chronic toxicities has already been reduced. Nevertheless, rates of complications requiring medical treatment range from 0.7-8% according to literature. 7.7% of patients develop severe complications after 5 years with an increasing risk for complications of 0.3%/year. Particularly, the volume of the small and large bowel receiving low doses (15 Gy) has been shown to be a predictive factor for the development of higher bowel toxicity. With the introduction of proton therapy into clinical practice, there are new opportunities for optimization of organ at risk-sparing thus possibly reducing toxicity.